Analysis of Inpatient Satisfaction Levels At Primaya Hospital Tangerang - Kornelius Andriansa Schubel Girsang (Institute of Computer Science (IOCS), 2021)
This study was conducted to determine the level of patient satisfaction at Primaya Hospital Tangerang based on the respondent's profile and the specified variables. This study involved 476 inpatients at Primaya Hospital Tangerang in the period December 2020. Data collection was carried out using data from a questionnaire containing 35 statements with a Likert Scale of 1-4 based on the purposive sampling method. Data were described and analyzed based on PLS. The results of this study analyzed the level of satisfaction of inpatients based on a specific respondent's profile for each variable used, namely health workers, health facilities, medical support and administrative processes in hospitals.